Study of Interactions between Metallothionein and Cisplatin by using Differential Pulse Voltammetry Brdicka´s reaction and Quartz Crystal Microbalance (Sensors, 2009)
Treatment strategies for tumour diseases are progressively focusing on personalization of medicine. However, this focus requires methods revealing the early general biological mechanisms, including the formation anti-cancer drugs’ resistance. The low molecular mass protein metallothionein is thought to be the crucial for the formation of resistance in tumour treatment based on the platinum-cytostatics. The interactions between metallothionein (MT) and cisplatin were determined by the adsorptive transfer stripping technique coupled with the differential pulse votlammetry Brdicka´s reaction. The signals related to the MT-cisplatin complex appeared at -0.9 V. The formation of this complex depended on the time of interaction between cisplatin and MT. The complex formation was consequently confirmed by quartz crystal microbalance analyses. The formation of this complex was detectable even after a 20 s long interaction. Moreover, we detected presence of MT-cisplatin complex in the blood of male rats treated with this drug.